Improving the Water Repellency of Polyester Filament Yarn and Fabrics - Garip, Beysim; Yüksel, Ayten; Ünal, Seda; Bedeloğlu, Ayşe (Ege Üniversitesi, 2023)
Water-repellent finishing is one of the most applied finishing processes by using materials that prevent the wetting of textile products and the passage of water drops. Fluorinated compounds are widely used in conventional methods applied for the development of water repellency, but the threats posed by these to humans and the environment have led to new searches for water repellency. Giving the water-repellent effect by reinforcing the masterbatch during fiber production can provide longer-lasting, homogeneously dispersed and environmentally friendly products. This reason, in this study, filament yarns containing fluorine-free water-repellent additives in three different weight percentages and fabrics coated with a water-repellent finishing without fluorine were produced. Then, the performance properties of the yarns were analyzed and water repellency, tensile and air permeability tests of the fabrics were performed. As coating repetition increased, the water repellency of the fabrics improved and air permeability decreased by approximately 80%.
1139B411900908
Keywords: Wearable Materials; Giyilebilir Malzemeler